2001
DOI: 10.1007/s002130000551
|View full text |Cite
|
Sign up to set email alerts
|

Effects of centrally administered orexin-B and orexin-A: a role for orexin-1 receptors in orexin-B-induced hyperactivity

Abstract: The present study has demonstrated a number of behavioural, neuroendocrine and neurochemical effects of orexin-B that distinguish it from orexin-A. Further, we have demonstrated a role for OX1 receptors in the actions of orexin-B upon motor activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
45
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(48 citation statements)
references
References 29 publications
2
45
0
1
Order By: Relevance
“…Here we extended these findings by showing a dose-related reduction in plasma prolactin following NmU (0.3-3 μg). Similar reductions in plasma prolactin levels are seen following i.c.v.-administered orexin-A (Hagan et al 1999;Jones et al 2001) and suggest that these neuropeptides may be involved in the inhibitory control of prolactin. One candidate for this role is DA, which when released from DA neurons in the tuberoinfundibular pathway potently inhibits prolactin release from the pituitary (Ben-Jonathon et al 1989).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Here we extended these findings by showing a dose-related reduction in plasma prolactin following NmU (0.3-3 μg). Similar reductions in plasma prolactin levels are seen following i.c.v.-administered orexin-A (Hagan et al 1999;Jones et al 2001) and suggest that these neuropeptides may be involved in the inhibitory control of prolactin. One candidate for this role is DA, which when released from DA neurons in the tuberoinfundibular pathway potently inhibits prolactin release from the pituitary (Ben-Jonathon et al 1989).…”
Section: Discussionmentioning
confidence: 56%
“…administration of neuropeptides. For example, striatal and hypothalamic 5-HT metabolism are altered by orexin-B (Jones et al 2001). NmU significantly elevated 5-HT levels in the frontal cortex and hypothalamus, with both increased levels of 5-HT and decreased levels of its metabolites in the hypothalamus and hippocampus, suggesting decreased 5-HT utilisation.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, the behaviors observed after hypocretin injection are similar to those observed during stress (Ida et al, 2000a), although they are less anxiogenic that the ones observed after CRF administration (Hagan et al, 1999). The hypocretins induce an intense grooming response accompanying the increase in arousal and locomotor activity (Hagan et al, 1999;Samson et al, 1999;Nakamura et al, 2000;Jones et al, 2001). These behavioral effects of hypocretins are blocked by an hcrt-r1 antagonist (Duxon et al, 2001).…”
Section: Discussionmentioning
confidence: 76%
“…Finally, central application of orexins elicits active arousal and hyperactivity in rats, an effect prevented by SB-334867 (Hagan et al, 1999;Jones et al, 2001). Together, these results suggest that Ox neurons promote locomotion and behavioral arousal and thus contribute to the maintenance of W by enhancing locomotion.…”
mentioning
confidence: 72%